CONTINGENCY, FORM AND JUSTICE (Andamios, Revista de Investigación Social, 2010)
This paper seeks to analyze some of the problems where contemporary political thought is being confronted. By contextualizing the terms return and crisis, this paper articulates three moments. First, it is claimed that the contemporary notion of politics can be characterized by the notion of the contingency. Second, from the previous assumptions, the specificity of political modernity is presented in the notion of form. Third, we point out simultaneously the point of view which acknowledges the irreducibility of politics as economy of violence and the reemergence of the problem of justice.
Keywords: Contingency; crisis; form; justice; violence